2017
DOI: 10.1094/cchem-07-16-0197-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saline Organic Acid Solutions Applied During Wheat Tempering on Flour Functionality

Abstract: Cereal Chem. 94(3):502-507Previously, we showed that tempering with saline organic acid solutions can reduce the aerobic plate count of wheat by as much as 4.3 log CFU/g. The purpose of this study was to evaluate the impact of these tempering solutions on the functional properties of resulting whole grain (WGF) and straight-grade (SGF) flours. Wheat was tempered to 15.5% moisture by tempering with sterile distilled water (control) or solutions containing NaCl (26% [w/v]) together with organic acid (acetic or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
6
11
0
Order By: Relevance
“…There are inherent differences in the endosperm characteristics between hard and soft wheat that could help explain the observed differences in acid content. These results were in agreement with a previous study, where it was reported that saline organic acid solutions applied during hard wheat tempering to reduce microbial load did not significantly change the pasting properties of the resulting straight-grade flours (Sabillón et al, 2017). Therefore, the capillary spaces between the endosperm starch granules in soft wheat may have facilitated the diffusion of organic acids, thus reaching a higher internal acid concentration.…”
Section: Effect Of Acidic Saline Solutions On Flour Functional Propsupporting
confidence: 92%
See 2 more Smart Citations
“…There are inherent differences in the endosperm characteristics between hard and soft wheat that could help explain the observed differences in acid content. These results were in agreement with a previous study, where it was reported that saline organic acid solutions applied during hard wheat tempering to reduce microbial load did not significantly change the pasting properties of the resulting straight-grade flours (Sabillón et al, 2017). Therefore, the capillary spaces between the endosperm starch granules in soft wheat may have facilitated the diffusion of organic acids, thus reaching a higher internal acid concentration.…”
Section: Effect Of Acidic Saline Solutions On Flour Functional Propsupporting
confidence: 92%
“…In a previous study, similar trends in pH and acid content were observed in the straight-grade flour obtained from hard wheat tempered with saline organic acid solutions (Sabillón et al, 2017). However, when comparing the acidity profile of flours between the two wheat classes studied, a higher acid content was observed in soft wheat.…”
Section: Effect Of Acidic Saline Solutions On Flour Functional Propsupporting
confidence: 78%
See 1 more Smart Citation
“…In a further study, the impact of tempering solutions on the functional properties of resulting whole‐grain (WGF) and straight‐grade flours (SGF) was evaluated and it was found that tested solutions had different effects on the properties of each type of flour. While tempering solutions did not have significant overall effects on pasting or mixing properties of SGF, treatment of WGF resulted in a numeric decrease in several pasting parameters and an increase in bread grittiness, indicating limited penetration of the organic acids into the endosperm of the grain (Sabillon, Bianchini, Stratton, & Rose, ).…”
Section: Current and Potential Techniques For Control Of Microbial Spmentioning
confidence: 99%
“…Partially ionized gas consisting of highly reactive chemical species r Efficiency of the method depends on the specific properties of the food product and its surface Niemira (2012); Schlüter et al (2013) Organic acids Antimicrobial agents due to the reduction of the environmental pH r Can increase moisture content and penetrate into the endosperm of grains Sabillon et al (2016Sabillon et al ( , 2017; Ölmez and Kretzschmar (2009) Microwave energy can also be used for control of stored-grain insects (Vadivambal, Jayas, & White, 2007). Pulsed ultraviolet (UV) light treatment.…”
Section: Future Trends For Decontamination Of Cereal Grainsmentioning
confidence: 99%